Hubungan Tingkat Kecukupan Energi dan Lemak dengan Status Gizi (Overweight) pada Orang Dewasa di Desa Babakan - Dea Aisyah Nurfadilah; Ana Dina, Resa; Fajriah, Elsa; Zahra, Alifa (Politeknik Negeri Madura, 2023)
In the era of globalization, changes in lifestyle and eating patterns are experienced by Indonesian people, so that one of the nutritional problems, namely overweight, is increasing. The total world population that is overweight is 2.1 billion in developed and developing countries. Therefore, this research was conducted to determine the relationship between the level of energy and fat consumption with the nutritional status of adults. This research used a cross-sectional design conducted in Babakan Village, Dramaga, Bogor Regency on August – November 2023. The subjects were 67 adults aged 20 – 40 years who were taken using systematic random sampling. Data were collected on body weight and height using a questionnaire and levels of energy and fat adequacy based on 24 hour recall. Statistical tests use normality tests and relationship tests use Pearson and Spearman. The results showed that the level of energy adequacy (p value>0.05) and fat (p value>0.05) did not have a significant relationship. However, data show that the higher the level of energy and fat adequacy, the higher the BMI and nutritional status of a person. Additionally, a significant portion of the adult population in Babakan has insufficient levels of energy and fat, namely 85% energy and 67% fat. It is recommended that the community in Babakan pay more attention to achieving a balanced diet to ensure nutritional needs are met. Furthermore, regular monitoring of weight and height is advised to keep track of nutritional status.